1992
DOI: 10.1007/bf01288467
|View full text |Cite
|
Sign up to set email alerts
|

Prompt fission induced by antiproton annihilation at rest on heavy nuclei

Abstract: Antiproton induced fission probabilities of U 23s, Bi 2~ Pb 2~ and Au 177 are reported together with the mass distribution of the fission fragments in the U 238 and Bi 2~ cases. The charged particles multiplicities observed in coincidence with fission have, also, been measured for U and Bi and are presented. PACS: 25.70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…It represents, in effect, the efficiency of the magnetic field in confining the plasma while simultaneously providing a measure of the power density generated by the reactor. Several studies (Bocquet et al, 1992;Machner et al, 1992) in recent years have shown that "at resf annihilation of antiprotons in U^^^ leads to fission at nearly 100% efficiency. values (-0.90) where no large scale instabilities of any sort that could lead to rapid breakup of the plasma were detected.…”
Section: R=^^-mentioning
confidence: 99%
See 1 more Smart Citation
“…It represents, in effect, the efficiency of the magnetic field in confining the plasma while simultaneously providing a measure of the power density generated by the reactor. Several studies (Bocquet et al, 1992;Machner et al, 1992) in recent years have shown that "at resf annihilation of antiprotons in U^^^ leads to fission at nearly 100% efficiency. values (-0.90) where no large scale instabilities of any sort that could lead to rapid breakup of the plasma were detected.…”
Section: R=^^-mentioning
confidence: 99%
“…Recent physics studies (Bocquet et al, 1992) have shown that "at resf' armihilation of antiprotons in the uranium isotope U^^^ leads to fission at nearly 100% efficiency. Under these conditions the plasma behaves much like a fluid, and its escape from the mirror is analogous to the flow of a gas into vacuum from a vessel with a hole.…”
Section: Fusion Propulsion Systemmentioning
confidence: 99%
“…Under these conditions the plasma behaves much like a fluid (gas in this case), and its escape from the system would be analogous to the flow of a gas into vacuum from a vessel with a hole. The condition for plasma confinement in GDM is given by 9 L R λ << (7) where λ is the collision mean free path, L the length of the plasma, and R the plasma mirror ratio defined by American Institute of Aeronautics and Astronautics In the above expression, denotes the vacuum mirror ratio, and as mentioned above β denotes the ratio of the plasma pressure to the (vacuum) magnetic field pressure. An expression of λ appropriate for the system under consideration can be written as…”
Section: Figure 2 Muon-boosted Fusion Propulsion Systemmentioning
confidence: 99%
“…Nuclear fission following the at rest annihilation of antiprotons in heavy nuclei has been demonstrated in uranium and bismuth among others, and measurements have been made of the mass distribution of the fission fragments, as well as the multiplicity of the charged particles that were emitted in the process. It was shown, for example 7 , that in the case of uranium the average masses and kinetic energies of the fission fragments are 212 amu and 160 MeV, respectively. In addition to the fission fragments, the annihilation products, namely the pions, are also ejected in addition to about 20 high energy neutrons.…”
mentioning
confidence: 99%
“…The vacuum chamber holding the torsion balance, the balance arm holding the uranium foil, and the antiproton beam optics have been constructed through NIAC support. It is well established that antiprotons induce fission when annihilating against heavy nuclei such as uranium (Bocquet, 1992). Because on average one fission fragment propagates into the sail while the other has a trajectory away from the sail, the absorption of the momentum of the ingoing fragment transfers momentum to the sail, and hence the spacecraft.…”
Section: Introductionmentioning
confidence: 99%